Nursing Care during the Perioperative within the Surgical Context - Salazar Maya, Ángela María (Investigación y Educación en Enfermería, 2023)
The study describes basic nursing care during the perioperative. Introduces the origins of perioperative nursing, general care that must be practiced with patient in this context. During the preoperative, care related with risk assessment and preparation of patient from the emotional and physical point of view are important. The trans-operative is related with the anesthesia used, surgical position, preparation of the skin, maintenance of normothermia, among many others. The postoperative depends on the type of anesthesia and surgical procedure, emphasizing on airway permeability, hemodynamic stability, pain, and symptomatology being presented by patients until they are stable and suitable for transfer to another service or their home.